Sedimentological implications of the change in the coverage of mangrove forest in Boca Zacate, Térraba-Sierpe National Wetlands, Costa Rica - Silva Benavides, Ana Margarita (2015)
In the last sixty years many geomorphological changes have occurred in Costa Rica's Térraba-Sierpe National Wetlands. Changes in coastal geomorphology are generally associated with erosion or accretion of sediment, which has led to the removal of sections of mangrove forests or sediment banks colonized by mangroves. The aim of this study was to analyze sedimentation as a leading process in the dynamics of coastal morphology and its implications for mangrove forest cover in the Boca Zacate area of Térraba-Sierpe wetlands. The study was conducted in the sectors of Bocón, Brujo and Coco Island in Boca Zacate, from 2008 to 2013. The research was based on a multi-temporal analysis of coastal morphology using aerial photographs from the years 1948, 1960, 1974, 1978, 1984, 1992 and 2011. The following measurements were also performed: monthly sedimentation rate (g/cm2/day), and granulometric composition and content of chemical elements in the sediments of the study area. These last two measurements were performed once each in the dry and rainy seasons during the years of study. The results indicated that over the past 60 years, Boca Zacate has witnessed a process of sustained erosion; from 1948 through 2001, losing 10.6 % of its land and approximately 8.9 % of its forest cover. It has also experienced accretion in the area of Coco Island. The Brujo sector showed the highest sedimentation rate and the Camibar estuary, the lowest. The dominant type of sediment in all study sites was sand, followed by clay and silt. The most widespread chemical elements (mg/L) included magnesium, calcium and potassium; others, such as manganese, iron, aluminum, phosphorus, zinc and copper, were measured in smaller amounts. Transport, composition and quantity of sediment in Boca Zacate are crucial to the changes that have occurred on the coastal area of La Boca, where the presence of dead trees was evident. This geomorphological analysis holds great importance for future guidelines and actions for the conservation and integrated management of the mangrove in Terraba- Sierpe National Wetlands.